2021
DOI: 10.1113/jp280581
|View full text |Cite
|
Sign up to set email alerts
|

Gut peptide regulation of food intake – evidence for the modulation of hedonic feeding

Abstract: The number of people living with obesity has tripled worldwide since 1975 with serious implications for public health, as having obesity is linked to a significantly higher chance of early death from associated comorbidities (metabolic syndrome, type 2 diabetes and cardiovascular disease). As obesity is a consequence of food intake exceeding the demands of energy expenditure, efforts are made to better understand the homeostatic and hedonic mechanisms governing food intake. Gastrointestinal peptides are secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 306 publications
1
14
0
Order By: Relevance
“…Finally, we found that fasting ghrelin was significantly lower in obese participants, and after controlling for BMI, it was negatively correlated only with WtHR [ 3 ]. Fasting ghrelin decreases with obesity and increases by diet-induced weight loss [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we found that fasting ghrelin was significantly lower in obese participants, and after controlling for BMI, it was negatively correlated only with WtHR [ 3 ]. Fasting ghrelin decreases with obesity and increases by diet-induced weight loss [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extending from its simplistic description as an imbalance between energy intake and expenditure, obesity ensues from multifaceted interactions between genetic, environmental, psychological, lifestyle, and dietary factors, making it a complex disease to understand and address [ 2 ]. Specifically, a growing body of evidence supports the role of the gut–brain axis in the pathogenesis of obesity [ 3 ]. On the one hand, the brain signals to the gut via efferent vagal and neuroendocrine pathways [ 4 ], and on the other hand, peptide hormones act as signaling molecules [ 5 ], triggering autonomic reflexes to regulate appetite, energy, and glucose homeostasis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mimicking the native physiology of INSL5-RXFP4 via Di recapitulated these results, whereas chemogenetic cell activation via Dq suppressed HFD and HPM intake. Selective chemogenetic activation of Rxfp4 -expressing cells in the VMH alone (targeted via rAAV-Dq) also suppressed HFD and HPM intake, reflecting their position in brain circuits implicated in homeostatic and hedonic regulation of food intake(20). Ablation of the VMH Rxfp4 -positive cell population resulted in lower HFD consumption and body weight, mirroring the phenotype of global Rxfp4 knockout mice (4) and supporting the conclusion that Rxfp4 neurons in the VMH play a role in the physiological drive to consume highly palatable foods.…”
Section: Discussionmentioning
confidence: 99%
“…Mimicking the native physiology of INSL5-RXFP4 via Di recapitulated these results, whereas chemogenetic cell activation via Dq suppressed HFD and HPM intake. Selective chemogenetic activation of Rxfp4 -expressing cells in the VMH alone (targeted via Cre-dependent rAAV-Dq) also suppressed HFD and HPM intake, reflecting their position in brain circuits implicated in homeostatic and hedonic regulation of food intake [ 21 ]. Ablation of this population further demonstrated the importance of these neurones in governing long-term feeding behaviour.…”
Section: Discussionmentioning
confidence: 99%